The content of materials and didactic requirements for the formation of the student's ecological thinking in the teaching of "Natural Science" in the 4th grade - Sunnatulla Dostov (Peerian Journals Publishing, 2023)
This article describes in detail the contents of the materials and the didactic requirements for the formation of the student's ecological thinking in the IV grade of science, the educational components of science teaching in general secondary schools, and interdisciplinary connections in mastering natural science concepts.
Keywords: natural science; interdisciplinary connections; ecological thinking